Characterisation of a secreted immunogenic protein, phase-1 flagellin (FliC) of Salmonella enterica subspecies enterica Brandenburg : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Microbiology at Massey University, Palmerston North, New Zealand - Perera, Kalyani (Massey University, 2007)
Cell-envelope associated and secreted proteins of Salmonella are integral for host-pathogen interactions, and for the induction of protective immune responses. An array of exported proteins of S. Brandenburg was identified through constructing an expression library using alkaline phosphatase gene technology. A partial digest of S. Brandenburg strain S59 was cloned into the vector pJEM11, and expressed in E. coli. The DNA inserts from randomly selected alkaline phosphatase positive clones were sequenced, and the sequences were analysed using public databases to find the ones that may play a role in host immune cell activation. The phase-1 flagellin (fliC) gene identified from an alkaline phosphatase positive phenotype was chosen for further studies. The complete nucleic acid sequence of the fliC gene was obtained by PCR amplification. The complete ORF, part of the variable region (V456) and region IV (V4) of the fliC gene were cloned into the pET14b vector for the expression of N-terminal histidine-tagged fusion proteins. The proteins were purified through metal affinity chromatography, and were evaluated for their humoral immunogenic properties by Western blotting with sera collected from 81 sheep naturally infected with S. Brandenburg. All 81 naturally infected sheep had IgG antibodies against recombinant FliC, V456, and V4 proteins. Furthermore, Western blotting of sera from 6 salvexinTM+B-vaccinated sheep (Trial 2004) had IgG antibodies against the 3 recombinant proteins. Whole blood cells of vaccinated sheep did not show interferon-gamma production upon stimulation with recombinant FliC and V456 proteins. Western blotting of sera from sheep vaccinated with salvexinTM and salvexinTM+B (Trial 1999), and those from rabbits vaccinated with S. Brandenburg, S. Hindmarsh and S. Typhimurium suggested that recombinant V4 contains epitopes specific for S. Brandenburg. Therefore, V4 was used to develop a novel indirect enzyme-linked immunosorbent assay (ELISA) for the detection of serum IgG antibodies in S. Brandenburg infected sheep. The ELISA showed a specificity of 100%, and a sensitivity of 93.8%. Furthermore, a new PCR assay was developed targeting rfbJ(B) gene in a single reaction, and genes invA, fliC and fljB in a multiplex reaction for the identification of S. Brandenburg from pure cultures. The sensitivity and specificity of the PCR assay was calculated to be 100%.
Keywords: Salmonella genetics; Characterisation; Enzyme-linked immunosorbent assay; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300507 Microbiology (excl.virology)